2014
DOI: 10.1007/s00405-014-3200-6
|View full text |Cite
|
Sign up to set email alerts
|

Fundamental frequency, sound pressure level and vocal dose of a vocal loading test in comparison to a real teaching situation

Abstract: Vocal loading capacity is an important aspect of vocal health, especially for people in vocally demanding occupations such as teaching. To analyze vocal loading, vocal loading tests (VLTs) or portable voice devices such as accelerometers have been used. However, it remains unclear how much a VLT in a clinical setup reflects the vocal effort of a real situation, in particular for teachers in a given classroom lesson. In this study of vocally healthy 101 student teachers, we analyzed different vocal doses for a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
22
0
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 35 publications
(25 citation statements)
references
References 31 publications
0
22
0
3
Order By: Relevance
“…An abrupt increase in vocal loading was closely related to a harsher subjective self-reported rating [30]. Echternach et al found that a 10-min intensive VLT with a >80 dB loudness level was comparable to a 45-min teaching task in terms of vocal dose [31]. Remacle et al showed that kindergarden teachers had significantly greater distance doses than elementary school teachers based on an investigation of 12 kinderdarten and 20 elementary school female teachers [5].…”
Section: Introductionmentioning
confidence: 99%
“…An abrupt increase in vocal loading was closely related to a harsher subjective self-reported rating [30]. Echternach et al found that a 10-min intensive VLT with a >80 dB loudness level was comparable to a 45-min teaching task in terms of vocal dose [31]. Remacle et al showed that kindergarden teachers had significantly greater distance doses than elementary school teachers based on an investigation of 12 kinderdarten and 20 elementary school female teachers [5].…”
Section: Introductionmentioning
confidence: 99%
“…The same proportion of teachers talked with raised voice levels, ≄86 dB (at 0.1 m), and no teacher used a relaxed level ≀74 dB (at 0.1 m). There have so far been no reliable reference values, especially for voice SPL recorded by means of a portable voice accumulator, although some data [22, 23] have been published. This study confirms the correlation between noise levels and voice loudness (voice SPL) as shown in both the laboratory environment [12] and field investigations [22].…”
Section: Discussionmentioning
confidence: 99%
“…There have so far been no reliable reference values, especially for voice SPL recorded by means of a portable voice accumulator, although some data [22, 23] have been published. This study confirms the correlation between noise levels and voice loudness (voice SPL) as shown in both the laboratory environment [12] and field investigations [22]. Our results also showed that the change in voice loudness followed the change in the activity noise levels and that the majority of the teachers increased the loudness of their voices up to 9 dB apace with the increasing noise level.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations